2020
DOI: 10.1177/0309524x20983220
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of the effects of ice accretion on the aerodynamic and structural behavior of offshore wind turbine blade

Abstract: In recent years, several wind turbines have been installed in cold climate sites and are menaced by the icing phenomenon. This article focuses on two parts: the study of the aerodynamic and structural performances of wind turbines subject to atmospheric icing. Firstly, the aerodynamic analysis of NACA 4412 airfoil was obtained using QBlade software for a clean and iced profile. Finite element method (FEM) was employed using ABAQUS software to simulate the structural behavior of a wind turbine blade with 100 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…The wind turbine is driven by the resultant force. Therefore, when the incoming wind flow AoA changes, the force on the airfoil will also change [32]. According to the engineering practice, the AoA of 0 • to 20 • is the common range of attack angle.…”
Section: Ice Accretion Simulationmentioning
confidence: 99%
“…The wind turbine is driven by the resultant force. Therefore, when the incoming wind flow AoA changes, the force on the airfoil will also change [32]. According to the engineering practice, the AoA of 0 • to 20 • is the common range of attack angle.…”
Section: Ice Accretion Simulationmentioning
confidence: 99%
“…However, icing and foggy weather were identified as critical factors, the impact of which need to be included in the estimation of performance metrics. In another study, a simple model using two different positions of rotating blades was employed by Lagdani et al [59] to examine and compare clean and iced profiles of blades with NACA4412 cross-sections. They linked the degradation in the performance of the turbine with accumulation of ice on the leading edge of a blade.…”
Section: Excitation Of Foundation Platformsmentioning
confidence: 99%
“…Oumnia and Kangash et al simulated the aerodynamic and structural performance of a wind turbine on an iced-up NACA 4412 airfoil and a NACA 64-618 airfoil. The results showed that when ice accumulates on the surface of a blade, the shape of its profile is changed, the lift and drag coefficients change significantly, and the aerodynamic and structural performance of the wind turbine is degraded [21,22]. Jin et al investigated the aerodynamic characteristics of S832 and S826 airfoils with icing profiles based on CFD numerical analysis, and the CFD analysis showed that the airflow behavior of iced blades changed compared with that of un-iced blades, which led to the degradation of aerodynamic performance, and that the change in the aerodynamic characteristics of S832 was more obvious than in S826 [23].…”
Section: Introductionmentioning
confidence: 99%